Modified predictive control for both normal and LVRT operations of a Quasi-Z-Source Matrix Converter based WECS. (November 2017) - Alizadeh, Mojtaba; Kojori, Shokrollah Shokri
Abstract: A new Wind Energy Conversion System (WECS), a Permanent-Magnet Synchronous Generator (PMSG) fed by a Quasi-Z-Source Matrix Converter (qZSMC), is proposed. At the same time, the paper proposes a Modified Predictive Control (MPC) for both normal and Low Voltage Ride-Through (LVRT) operations of the proposed WECS. First, the qZSMC comprised of a Three-Phase Quasi-Z-Source Network (TPQZSN) and a Matrix Converter (MC) is analyzed in both time and frequency domains. The TPQZSN is modeled using state–space averaging method and its transfer functions are derived. The transfer functions are then analyzed using Bode plot, and eventually a guide to select the proper passive components of the qZSMC is rendered. A MPC is proposed to control grid-side quantities while the generator speed is controlled by shoot-through adjustment. Unlike the Traditional Predictive Control (TPC), the proposed MPC can be applied to z-source converters, while considerably reducing output current ripples. The proposed control system is further adapted to enhance LVRT capability of the proposed WECS. The performance of the proposed WECS is evaluated under both normal and abnormal working conditions, comparing it with the Traditional MC-based PMSG-WECS (TMC-WECS).